An Overview Of Intrusion Detection System Using Various Classification Concepts - Shukla, K; Gupta, RK; Namdeo, V (International Journal of Computer Sciences and Engineering, 2025)
As technological interconnection and digital communication schemes wide spreading, data accessing required to be kept in sharing environment and hence it will surely lead to compromise the data in many aspects. So to keep data secure and protected there are variety of techniques and tools also developed and Intrusion detection system (IDS) is one of them. IDS system conceptualized with identifying the intrusions in place of stopping the attacks. There are various techniques discussed here in context of signature and behavior based IDS. These IDS tools use different identification techniques to classify and identify the attacks and type of attacks. This paper includes different types IDS which has capability inclusion of identifying attacks like probe, DoS, R2L etc. It is also covering categorized descriptions of host based as well as network based hybrid intrusion detection systems.